Faktor-Faktor Yang Berhubungan Dengan Kejadian Preeklamsia Pada Ibu Hamil Di RSU Bunda Margonda Tahun 2019 - Ningsih, Nurul Syuhfal; Situmeang, Irene Florensia (Bunda Edu-Midwifery Journal (BEMJ), 2022)
The maternal mortality rate due to preeclampsia in Indonesia is between 15% to 25%. The purpose of this study was to determine the factors associated with the incidence of preeclampsia in pregnant women at Bunda Margonda General Hospital in 2019. The method used is descriptive analytic method with a cross-sectional approach. The analysis used is univariate and bivariate. From the results of the study, it is known that there is a significant relationship between age [P value = 0.031], parity [P value = 0.015], pregnancy distance [P value = 0.008] and there is no significant relationship with education [P value = 0.786].